2020
DOI: 10.3390/children7110231
|View full text |Cite
|
Sign up to set email alerts
|

Reach, Recruitment, Dose, and Intervention Fidelity of the GoActive School-Based Physical Activity Intervention in the UK: A Mixed-Methods Process Evaluation

Abstract: School-based multi-component physical activity (PA) promotion is advocated; however, research has indicated that a multi-component approach may not always be effective at increasing adolescent PA. Evaluation of the GoActive 12-week multi-component school-based intervention showed no effect on adolescent PA. A mixed-methods process evaluation was embedded to facilitate greater understanding of the results, to elicit subgroup perceptions, and to provide insight into contextual factors influencing intervention im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
(66 reference statements)
0
12
0
1
Order By: Relevance
“…Although there is limited evidence for remote interventions with adolescents [ 37 ], a previous intervention involving adults identified significant positive improvements in MVPA and intrinsic motivation [ 38 ]. Schools are an obvious site from which to base youth PA interventions, however several issues are commonly cited when working in the school environment, such as timetabling constraints [ 39 ], inconsistencies in intervention implementation [ 40 ], varied availability of equipment and facilities [ 41 ], and lack of teacher adoption [ 42 ]. HERizon attempted to overcome such barriers as the intervention arms were not bound to a set location or weekly time slot.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is limited evidence for remote interventions with adolescents [ 37 ], a previous intervention involving adults identified significant positive improvements in MVPA and intrinsic motivation [ 38 ]. Schools are an obvious site from which to base youth PA interventions, however several issues are commonly cited when working in the school environment, such as timetabling constraints [ 39 ], inconsistencies in intervention implementation [ 40 ], varied availability of equipment and facilities [ 41 ], and lack of teacher adoption [ 42 ]. HERizon attempted to overcome such barriers as the intervention arms were not bound to a set location or weekly time slot.…”
Section: Discussionmentioning
confidence: 99%
“…The stakeholders also recognised the positive impact the programme had on the students involved, alongside being active, such as skill development, which is likely to have implications for ongoing delivery. The benefits associated with being a student peer ‘mentor’ or ‘leader’ have been documented in past peer-led PA interventions [ 74 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, given that friend involvement can be an important factor affecting PA participation [ 25 , 26 ], recruiting friend groups could be used as a potential strategy [ 84 , 88 ] to increase recruitment. Other school-based PA interventions have found merit in providing small rewards to facilitate sustained involvement [ 73 , 76 ], such as sports bags or pens [ 76 ]. One stakeholder in this study suggested using different rewards, such as a ‘Girls Active Project’ t-shirt.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to quantify the influencing factors (92,96), and to analyze which influencing factors are interconnected. It is essential to analyze the factors that have an influence on implementation outcomes (97)(98)(99) and on health outcomes (100). Choosing appropriate implementation strategies (101) and organizing the whole process with an overall evaluation plan (33) should be the standard in implementation evaluation in general and in children with low SES in particular.…”
Section: Methodological Considerations-for Researchermentioning
confidence: 99%